The Modeling of Electromagnetic Behavior in the High-Frequency Range of Al2O3 and TiO2 Thermoplastic Composites in Support of Developing New Substrates for Flexible Electronics - Radu F. Damian; Cristina Pachiu; Alexandra Mocanu; Alexandru Trandabat; Romeo Cristian Ciobanu (Crystals, 2025)
The paper describes the simulation of energy absorption in polymer micro-composites that include dielectric inserts (commercial Al2O3 and TiO2 particles, with three particle sizes of 1, 5 and 25 µm, respectively). The investigated frequency spectrum, mainly from 0.001 to 100 GHz, is designed for various uses as substrates in electronic technologies. The electromagnetic simulation software chosen was CST Studio Suite, which evaluates the power loss at different frequencies, playing a crucial role in creating the ideal structure of these substrates. The effective limits of the electromagnetic simulation are specified. It is shown that a considerable increase in absorption occurs, by a factor of 12 to 120, depending on the dielectric material used for the inserts and the mass ratio applied in the insertion technique. Dielectrics with high permittivity provide higher absorption, but also create a nonuniform field distribution within the material, resulting in a high peak-to-average absorption ratio. In scenarios where this behavior is intolerable, the technology must be carefully tuned to improve the consistency of the insertions in the substrate material. The final outcomes of the simulations indicated that for creating new substrates for flexible electronics, polyethylene composites with TiO2 insertions are suggested, particularly at lower concentrations of up to 7% and with a larger radius, such as 25 μm, which could offer significant economic advantages considering that the current concept advises the use of costly particles ranging from nanoscale particles to those 1 μm in size and a composition exceeding 10%.